1997
DOI: 10.1007/pl00000572
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of heat shock gene induction and expression during Drosophila development

Abstract: Some heat shock genes are expressed in the absence of stress during embryogenesis and metamorphosis in the fruit fly Drosophila melanogaster. Their functions in these processes are unknown. During development, each of the four members of the small heat shock protein family (Hsp27, Hsp26 Hsp23 and Hsp22), which are coordinately induced in response to a heat stress, shows a specific pattern of expression in diverse tissues and cells. This expression is driven through cell-specific enhancers in the promoter regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
1
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 110 publications
3
72
1
2
Order By: Relevance
“…The four classical small HSPs (HSP22, HSP23, HSP26, and HSP27) were all highly induced after a heat shock (Fig. 1B), consistent with previous findings (Marin et al ., 1996; Michaud et al ., 1997). Apart from CG14207 and CG13133, all the other small HSPs were also found to be heat‐inducible (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The four classical small HSPs (HSP22, HSP23, HSP26, and HSP27) were all highly induced after a heat shock (Fig. 1B), consistent with previous findings (Marin et al ., 1996; Michaud et al ., 1997). Apart from CG14207 and CG13133, all the other small HSPs were also found to be heat‐inducible (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a Hsp60 expression increase was observed in heart failure (Lin et al 2007;Wang et al 2010). It is known that Hsp27 is usually expressed in heart muscle tissues under normal conditions where its function can be modified by different cell mechanisms operating either on their expression or their structure depending on cellular localization (Michaud et al 1997;Anastasiya et al 2005). However, several studies have indicated that overexpression of Hsp27 protects cardiac myocytes against ischemic injury (Yamboliev et al 2000;Vander Heide 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The sequences which regulate the tissue-specific expression and the heat shock expression of D. melanogaster hsp26 have been shown to be located in different parts of the promoter. Three regions involved in spermatocyte-specific expression are identified downstream from −352, whereas the ovarian expression is dependent on the region (−522 to −352) (Cohen and Meselson 1985;Frank et al 1992;Michaud et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The sHsps have many different functions, both under stress and under non-stress conditions (Mestril et al 1986;Michaud et al 1997;Michaud and Tanguay 2003). Under stress conditions they have chaperone functions, protect the cytoskeleton and modulate the apoptotic process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation